Tourism and hospitality management - Kozak, Metin, 1968-; Kozak, Nazmi (Advances in culture, tourism and hospitality research ;, 2016)
The book aims to address topics such as tourism education and its development in the latter part of the twentieth century, taking "tourism<U+201d> to be a broader field than "hospitality." The term "hospitality" refers to all operations or services encompassing accommodation and food/beverage facilities at the micro level, whereas "tourism" stands for the other elements at the macro level, including business, destination, and transportation operations. Moving from the generic to the specific, this book is divided into three main parts. Part I starts from a more generic perspective, and is entitled "Tourism Management." It comprises seven chapters by 13 scholars. Part 2 has a more moderate focus, and is entitled "Hospitality Management". It includes seven chapters contributed by 15 scholars from across the world. Part 3 is entitled "Education and Training in Tourism and Hospitality", and covers a range of topics from both tourism and hospitality. This last part consists of six chapters contributed by 13 scholars from four continents.